Being in a loop: how long non-coding RNAs organise genome architecture. Issue 1 (9th April 2019) - Pisignano, Giuseppina; Pavlaki, Ioanna; Murrell, Adele
Abstract : Chromatin architecture has a significant impact on gene expression. Evidence in the last two decades support RNA as an important component of chromatin structure [ Genes Dev. (2005)19, 1635–1655; PLoS ONE (2007)2, e1182; Nat. Genet. (2002)30, 329–334]. Long non-coding RNAs (lncRNAs) are able to control chromatin structure through nucleosome positioning, interaction with chromatin re-modellers and chromosome looping. These functions are carried out in cis at the site of lncRNAs transcription or in trans at distant loci. While the evidence for a role in lncRNAs in regulating gene expression through chromatin interactions is increasing, there is still very little conclusive evidence for a potential role in looping organisation. Here, we review models for the involvement of lncRNAs in genome architecture and the experimental evidence to support them.